Synthesis and Evaluation of Monophosphoryl Lipid A Derivatives as Fully Synthetic Self-Adjuvanting Glycoconjugate Cancer Vaccine Carriers - Zhou, Zhifang (2014)
Fully synthetic carbohydrate-based cancer vaccine is an attractive concept, while an important topic in the area is to develop proper vaccine carriers that can improve the immunogenicity and other immunological properties of tumor-associated carbohydrate antigens (TACAs). In this context, four monophosphoryl derivatives of Neisseria meningitidis lipid A were synthesized via a highly convergent and effective strategy and evaluated as vaccine carriers and adjuvants. The conjugates of these monophosphoryl lipid A (MPLA) derivatives with a modified form of the sTn antigen were found to elicit high titers of antigen-specific IgG antibodies, indicating T cell-dependent immune response, in the absence of an external adjuvant. It was concluded that MPLA’s could be utilized as potent vaccine carriers and built-in adjuvants to create fully synthetic self-adjuvanting carbohydrate-based cancer vaccines. The lipid composition and structure of MPLA were shown to have a significant influence on its immunological activity, and among the MPLA’s examined, natural N. meningitidis MPLA exhibited the most promising properties. Moreover, Titermax Gold, a conventional vaccine adjuvant, was revealed to inhibit, rather than promote, the immunological activity of MPLA conjugates, maybe via interacting with MPLA text goes here.